Long-term trends in total cloud cover in the Arctic based on surface observations in 1985–2020 - Sviashchennikov, Pavel; Drugorub, Aleksandr (Bulletin of Geography. Physical Geography Series, 2022)
This paper provides an assessment of long-term trends in total cloud cover in the Arctic for the period 1985–2020 based on surface observations. Analysis shows that total cloud cover exhibits a substantial variation both between seasons and from year to year. Two areas of positive trends were found in the total cloud cover from October to April over the Arctic: one in the North Atlantic from 20° W up to 90° E and another from 150° E up to 150° W, which may be a result of atmospheric heat and moisture transport through the Atlantic and Pacific gates. Throughout the year, positive trends dominate over the Arctic Ocean and its seas (except for the Laptev Sea). Negative trends prevail over the continental parts of the Arctic